Energy evolution and damage ontology modeling of coal destruction at different water contents. - Yongjiang Yu; Jiaming Liu; Wenjing Guo; Zhiyuan Song; Yuntao Yang; Shangqing Zhao; Dong Xu; Zhiqiang Wu (PLoS ONE)
The aim of this study was to investigate the energy evolution characteristics and an ontological model of the deformation of coal under different water contents. Uniaxial compression tests were conducted for coal with different water contents, and the analyses were based on the energy principle and the principle of minimum energy dissipation. The results showed that the physical properties of the coal specimens were different under different water contents, the peak strain was positively correlated with water content, and the compressive strength and elastic modulus were negatively correlated with water content. Additionally, the compressive strength and elastic modulus of the coal specimens showed a steep and subsequent slow-change trend. From an energy perspective, the higher the water content of the coal specimens, the higher their energy dissipation at the peak; the smaller the limiting elastic strain energy, the lower the absorbed energy. The principle of minimum energy dissipation was used to deduce the energy evolution and mechanical properties of coal body damage under different water contents, deriving the initial and critical values of damage. The water content of the coal specimens was positively correlated with their initial and critical values of damage, and the relationship with water content was nonlinear. This result was used to establish a stress-strain ontology model for coal rocks with different water contents under uniaxial compression. The model is an improvement over traditional ontology models, addressing the problem of low accuracy in simulations of materials at the compaction stage.